2013
DOI: 10.2478/jppr-2013-0052
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Insecticidal Activities of Three Eucalyptus Species Cultivated in Iran, Against Hyphantria Cunea Drury (Lepidoptera: Arctiidae)

Abstract: In the current study, the larvicidal activity of leaf essential oils from three eucalyptus species (Eucalyptus largiflorens Meull, Eucalyptus oleosa Meull, and Eucalyptus spathulata Hook) against American white moth, Hyphantria cunea Drury 1773 (Lepidoptera: Arctiidae), was investigated. Mortality was recorded daily for three days after treatment. Leaf disc bioassays revealed that all three oils had strong insecticidal activity on the experimental insects insofar as 50% lethal concentrations (LC 50 ) for E. ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In that sense, for biological purposes, it could be more informative to 1: α-Pinene, 2: β-pinene, 3: β-myrcene, 4: limonene, 5: α-terpineol, 6: 1,8-cineole, 7: globulol. study the entire oil rather than some of its components because the concept of synergism seems to be important (Regnault-Roger et al, 2012;Ebadollahi et al, 2013).…”
Section: Insecticidal Activity Assaymentioning
confidence: 99%
“…In that sense, for biological purposes, it could be more informative to 1: α-Pinene, 2: β-pinene, 3: β-myrcene, 4: limonene, 5: α-terpineol, 6: 1,8-cineole, 7: globulol. study the entire oil rather than some of its components because the concept of synergism seems to be important (Regnault-Roger et al, 2012;Ebadollahi et al, 2013).…”
Section: Insecticidal Activity Assaymentioning
confidence: 99%
“…The development of alternative methods that are not chemical applications is necessary in pest management for the sake of human health and for the safety of the environment (Jafarbeigi et al 2012). The demand for natural insecticides (Ertürk et al 2004;Ebadollahi 2013) as well as the demand for pyrethrum as a botanical insecticide is rising rapidly in the world market (Andreev 2008;Li 2011). Its powder is prepared from dried flower heads.…”
Section: Introductionmentioning
confidence: 99%
“…α-Pinene has been known to show fumigant toxicity against Sitophilus oryzae, T. castaneum, and Triboleum confusum [62][63]. The effectiveness of 1,8-cineole has been documented against many storedproduct insects [22]. This implies that the higher the 1,8-cineole content, the lower the LC 50 values and vice versa.…”
Section: Fumigant Activitymentioning
confidence: 95%
“…Studies have also reported insecticidal activities of different species of Myrtaceae against T. castaneum [16][17][18]. α and β-pinene, terpinen-4-ol, 1,8-cineole, and methyl eugenol have been reported as major components in Myrtaceae essential oils, which have been known for their toxicities against pestiferous insects [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%